Emergency Department Workload and Crowding During a Major Electronic Health Record Breakdown - Wretborn, Jens; Ekelund, Ulf; Wilhelms, Daniel B. (Frontiers in Public Health, 2019)
Background: Emergency Departments (EDs) today rely heavily on Electronic Health Records (EHRs) and associated support systems. EHR updates are known to be associated with adverse events, but reports on the consequences of breakdowns in EDs are lacking. Objectives: To describe the effects on workload, occupancy, patient Length Of Stay (LOS), and admissions at three EDs (a regional trauma center, a community hospital and a rural community hospital) during a 96 h period of EHR downtime, of which 48 h represented an unexpected breakdown. Methods: Assessments of workload, on a scale from 1 (no workload) to 6 (very high workload), were obtained from all staff before, during and after the downtime period. Occupancy, LOS and hospital admissions were extracted from data recorded in the fallback system at each ED during the downtime, and compared with the period before and after (uptime). Results: Workload increased considerably at two EDs during the downtime whereas the third ED lacked resources to assess workload due to the breakdown. The proportion of assessments ≥4 were 28.5% during uptime compared to 38.4% during downtime at the regional trauma center ED (difference 9.9%, p = 0.006, 95% CI 2.7–17%), and 22.9% compared to 41% at the rural community ED (difference 18.1%, p = 0.0002, 95%CI 7.9–28.3%). Median LOS increased by 19 min (3:56 vs. 4:15, p < 0.004) at the regional trauma center ED, by 76 min (3:34 vs. 4:50, p < 0.001) at the community ED and was unaltered at the rural community ED (2:47 vs. 2:51, p = 0.3) during downtime. Occupancy increased significantly at the community ED (1.59 vs. 0.71, p < 0.0001). Admissions rates remained unchanged during the breakdown. Fallback systems and initiatives to manage the effects of the breakdown differed between the EDs. Conclusions: EHR downtime or unexpected breakdowns increased staff workload, and had variable effects on ED crowding as measured by LOS and occupancy. Additional staff and digital fallback systems may reduce the effects on ED crowding, but this descriptive study cannot determine causality.